2020
DOI: 10.1002/2050-7038.12389
|View full text |Cite
|
Sign up to set email alerts
|

Three‐phase converter power control under grid imbalance with consideration of instantaneous power components limitation

Abstract: Summary This paper presents a control method of a three‐phase power converter operating under grid imbalance and harmonics. The proposed control system uses virtual flux of the grid, and a voltage fundamental harmonic to calculate reference instantaneous power oscillations, in order to maintain sinusoidal converter current. Thus, there is no need for symmetrical sequence decomposition. The presented method ensures current asymmetry corresponding to or opposite to voltage asymmetry, depending on the operation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, in the case of an imbalanced or asymmetric MG, the average of the 3-phase voltages results in an instantaneous, non-zero value due to the stochastic nature of the real-time loads connected to the MG. It is important to highlight again that this MG's neutral value (v gn ) is generally considered to be grounded in the literature [20][21][22][23] and negative sequence control schemes are used to compensate for the imbalances appearing in the form of a negative sequence in the MG. Contrarily, in this article, the mean voltage (v gn ) of the MG is kept floating and also it is used as an additional requirement of the MG, which is reflected towards the generation side (or the RES-based VSI source side) as a desired additional reference value. In order to obtain the desired results, it is specified in the error dynamics form as given below in Equation ( 7):…”
Section: System's Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the case of an imbalanced or asymmetric MG, the average of the 3-phase voltages results in an instantaneous, non-zero value due to the stochastic nature of the real-time loads connected to the MG. It is important to highlight again that this MG's neutral value (v gn ) is generally considered to be grounded in the literature [20][21][22][23] and negative sequence control schemes are used to compensate for the imbalances appearing in the form of a negative sequence in the MG. Contrarily, in this article, the mean voltage (v gn ) of the MG is kept floating and also it is used as an additional requirement of the MG, which is reflected towards the generation side (or the RES-based VSI source side) as a desired additional reference value. In order to obtain the desired results, it is specified in the error dynamics form as given below in Equation ( 7):…”
Section: System's Modelingmentioning
confidence: 99%
“…The sliding mode control (SMC) method has also been applied, considering that the converters have switching devices, which in nature are discontinuous and quite consistent with the adopted control technique [18,19]. However, all of these studies are found employing two-dimensional control, which results in the under-utilization of the capabilities of three-phase converters [20][21][22][23].…”
mentioning
confidence: 99%
“…Based on the instantaneous reactive power theory, voltage harmonics can be expressed, using the superposition of the DC component and AC components of various frequencies under the polar coordinate system, while three-phase imbalance can be presented as a non-zero negative sequence [22,35]. The microgrid power quality can be improved by controlling harmonic imbalance at various microgrid PCC nodes [36].…”
Section: The Strategy and Modelling Based On Harmonic Imbalance Princ...mentioning
confidence: 99%
“…Different fault-tolerant solutions to phase-unbalance have been proposed; one solution is to use a control method that can operate in both ideal and unbalanced modes. A fix to minimize the problem is to add hardware components to absorb the additional power ripple during phase unbalance [59,[67][68][69][70][71][72][73][74][75][76][77].…”
Section: General Classificationmentioning
confidence: 99%